Advances in Aquatic Invertebrate Stem Cell Research 2022
DOI: 10.3390/books978-3-0365-1635-6-1
|View full text |Cite
|
Sign up to set email alerts
|

<p>From Primary Cell and Tissue Cultures to Aquatic Invertebrate Cell Lines: An Updated Overview</p> <p>&nbsp;</p>

Abstract: He is a member of the editorial board of the Invertebrate Survival Journal and the European Journal of Zoology, and is a founding member of the Italian Association of Developmental and Comparative Immunobiology (IADCI). His main research interests are the evolution of innate immunity and the study of the cellular and molecular basis of immune responses in marine invertebrates, with particular reference to the role of hemocytes/coelomocytes in immune defense and, more generally, in the stress response. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 614 publications
0
5
0
Order By: Relevance
“…The world’s oceans and seas host hundreds of thousands of animal species, primarily invertebrates, with many types of cells that exhibit a wide range of cellular potentialities [ 38 ] and offer endless applications. Yet, while numerous cell lines have been commonly derived from vertebrates and terrestrial invertebrate taxa, e.g., insects and arachnids, until just recently [ 8 ], all efforts to develop cell lines from marine invertebrates have failed, despite many attempts made on a wide range of species over the past decades [ 1 , 2 , 3 , 6 , 7 , 9 ]. However, to establish a sustainable pharmaceutical industry based on the “blue economy”, the most viable approach is (a) to cultivate cells under controlled conditions by creating widespread “cell factories”, still an unaccomplished objective, and (b) to scale up cell cultures from marine organisms in bioreactors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The world’s oceans and seas host hundreds of thousands of animal species, primarily invertebrates, with many types of cells that exhibit a wide range of cellular potentialities [ 38 ] and offer endless applications. Yet, while numerous cell lines have been commonly derived from vertebrates and terrestrial invertebrate taxa, e.g., insects and arachnids, until just recently [ 8 ], all efforts to develop cell lines from marine invertebrates have failed, despite many attempts made on a wide range of species over the past decades [ 1 , 2 , 3 , 6 , 7 , 9 ]. However, to establish a sustainable pharmaceutical industry based on the “blue economy”, the most viable approach is (a) to cultivate cells under controlled conditions by creating widespread “cell factories”, still an unaccomplished objective, and (b) to scale up cell cultures from marine organisms in bioreactors.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, over 500 peer-reviewed publications have been published on this topic, with the main focus being on six phyla, which are Porifera, Cnidaria, Crustacea, Mollusca, Echinodermata, and Urochordata [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, until recently [ 8 ], not a single continuous cell line was established for any aquatic invertebrate taxon, as all efforts to obtain lasting proliferating cultures from marine invertebrates have inexplicably failed [ 1 , 2 , 9 ], despite the increasing demand of these cultures for a wide range of applications [ 5 , 6 , 7 , 8 , 10 , 11 ]. Further, it has been repeatedly shown that primary cultures of marine invertebrate cells cease dividing 24–72 h from onset [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostreobium strains were originally isolated from their coral host and propagated for 4.5 years with low doses of penicillin (100 U/mL) and streptomycin (100 µg/mL) antibiotics to prevent overgrowth by opportunistic bacteria [ 7 ]. Although routinely used in animal cell cultures, these generic antibiotics are known to be inefficient against most native marine bacteria [ 37 ]. Indeed, bacterial fatty acid markers were consistently detected within chloroform extracts of these strains [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Originally isolated from their coral host in the presence of low doses of penicillin (100 U/ml) and streptomycin (100 µg/mL) antibiotics, they were propagated for 4.5 years, with penicillin and streptomycin (Massé et al ., 2020) to prevent overgrowth by opportunistic bacteria. Although routinely used in animal cell culture, these generic antibiotics are known to be not efficient against most native marine bacteria (Domart-Coulon and Blanchoud, 2022). And, indeed, bacterial fatty acid markers were consistently detected within chloroform extracts of these strains (Massé et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%